THE QUALITY OF ANTENATAL CARE BASED ON INDEX SATISFACTION OF PREGNANT WOMEN - Nurmaliatul Firdaus; Aditiawarman Aditiawarman; Dwi Izzati Budiono (UNIVERSITAS AIRLANGGA, 2021)
AbstractBackground: Quality antenatal care in the MCH program is considered to be one of the effective efforts to reduce maternal and child morbidity and mortality. An indicator of the success of ANC services can be seen from the output produced, namely in the form of K4 coverage. According to Kotler there are 5 (five) determinants of service quality that can be used as a basis for assessing the level of customer satisfaction with the quality of service received including Tangibles, Reliability, Responsiveness, Assurance and Empathy. Method: This research method is quantitative descriptive with survey approach. The total sample of 149 pregnant women with total sampling techniques. The instrument used was a questionnaire. Data analysis uses univariate analysis. Results: The most valued statements both from each dimension namely; tangible: Midwife performance reliability: recording in the MCH handbook, responsiveness: responses to complaints, assurance: the nature of the Midwife, empathy of communication between midwives and patients. The most valued statements are enough from each dimension namely; tangible: examination room, reliability: service procedures, responsieness: midwife response to patients waiting for long queues, assurance: guarantee to service, empathy: suitability of waiting time and duration of service. Conclusion: The data shows that the majority of respondents considered the quality of antenatal services at the Tambakrejo Public Health Center to be good but still needed to be improved so that the assessment was sufficiently good.